STUDY EVALUATION OF OELTUA DAM IN KUPANG REGENCY, NUSA TENGGARA TIMUR - Losiana, Kania
Oeltua Dam is located in East Nusa Tenggara Province, Kupang Regency, Kupang Tengah District, Oeltua Village. This dam was built in 1997 with the purpose to save the water during rainy season and supply the water for people in downstream during the dry season. The purpose of this final assigment is to evaluate the design of Oeltua Dam, including the reliability of Oeltua Dam, due to climate change and the change of rainfall. The first step to evaluate this dam is analyze the flood discharge using synthetic unit hydrographs with several methods. The method was chosen based on Creager Curve is ITB-2, it is 36,9 m3/s. After that, analyze the reservoir routing, and the outflow discharge is 32,17 m3/s. The existing spillway capacity is 49,76 m3/s, which means, the spillway in Oeltua Dam still feasible to use. The normal water level (NWL) is at +374.4 m, and the flood water level (FWL) is at +377m. The lifetime of the dam is 30 years, and the dam is expected to be able to meet the water needs for 16.630 people. The outflow from the intake (at the elevation +368,5 m), will be used to whirl the turbine at the elevation +358 m. Which the type of the power plant is picohydro.